Visualization of Fibre Products Using ToF-SIMS and Multivariate Data Analysis - Leksuntrakorn, Jutima (My University, 2021)
Physical and chemical complexity of paper and fibre products, makes their spatial analysis challenging. In this study, the visualization of calendered papers was performed using spectroscopic technique, time-of-flight secondary ion mass spectrometry (ToF-SIMS), along with multivariate data analysis (MVDA) to resolve the chemical hierarchy. The chemical difference between the papers calendered at 100 C and 200 C was investigated by using principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA). Among the observed differences between each side of the papers, the largest variation occurred in lower-mass region (< m/z 100). Potential chemical changes that take place in the higher-mass range (> m/z 300) could not be observed clearly using ToF-SIMS. The findings of this study are essential in expanding the ToF-SIMS library of paper and paper components, and demonstrates that multivariate analysis methods are needed for resolving the differences in spectral data of hierarchical materials.
Keywords: ToF-SIMS; MVDA; paper composition